2012
DOI: 10.1111/j.1365-2559.2012.04306.x
|View full text |Cite
|
Sign up to set email alerts
|

Angiomyolipoma of the liver: a reappraisal of morphological features and delineation of new characteristic histological features from the clinicopathological findings of 55 tumours in 47 patients

Abstract: The majority of hepatic AMLs were myomatous in type, showing variable cellular morphology and growth patterns. Cellular atypia and invasive growth were frequent, indicating that hepatic AMLs often show malignancy-like histological features. Although the majority of cases behave as benign tumours, AML should be considered to have uncertain malignant potential, and careful follow-up of patients is recommended. Immunostaining for HMB-45 is specific for AML, and establishes the diagnosis. The occasional presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 21 publications
1
42
1
1
Order By: Relevance
“…Hepatic AMLs are sometimes misdiagnosed as HCCs because arterial enhancement and the presence of fat components are common in both lesions [78]. In addition, there are also lipid-poor AMLs which have no detectable fat components on imaging studies making the differentiation from other hypervascular tumors difficult [77,79]. According to a recent study which compared Gd-EOB-MRI features of lipid-poor AMLs and HCCs, both lesions showed similar dynamic enhancement patterns with arterial enhancement followed by hypointensity on the PVP or TP [80] (fig.…”
Section: Hcc Vs Non-hepatocellular Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hepatic AMLs are sometimes misdiagnosed as HCCs because arterial enhancement and the presence of fat components are common in both lesions [78]. In addition, there are also lipid-poor AMLs which have no detectable fat components on imaging studies making the differentiation from other hypervascular tumors difficult [77,79]. According to a recent study which compared Gd-EOB-MRI features of lipid-poor AMLs and HCCs, both lesions showed similar dynamic enhancement patterns with arterial enhancement followed by hypointensity on the PVP or TP [80] (fig.…”
Section: Hcc Vs Non-hepatocellular Tumorsmentioning
confidence: 99%
“…Features suggestive of ICCs rather than HCCs include i) the absence of fat and a tumor capsule [74], ii) central hypointensity on T2-weighted images [74], iii) a lower proportion showing arterial enhancement [75], iv) a target appearance on HBP images [16], and v) a target appearance on DWI [76]. Hepatic angiomyolipoma (AML) is a rare benign mesenchymal tumor which is composed of variable proportions of thick-walled vessels, smooth muscle cells, and adipose tissue [77]. As a result of the various percentages of mixed histologic components, hepatic AMLs can manifest with diverse imaging features [78].…”
Section: Hcc Vs Non-hepatocellular Tumorsmentioning
confidence: 99%
“…Some studies have suggested that abnormally large dilated vessels should be considered a typical histological feature of MHAMLs, 16,18,24 and might be important in recognizing, understanding and interpreting the findings of various imaging modalities. In the present study, abnormally large dilated vessels were present in 10 of the 12 tumours that were .4.0 cm.…”
Section: Discussionmentioning
confidence: 99%
“…It has diverse imaging features and mimics HCC to show arterial enhancement, intralesional fat, and washout. 58,59 In addition, lipid-poor angiomyolipoma has no detectable fat component on imaging or chemical shift imaging. 58,60 On Gd-EOB-MRI, both entities show similar dynamic enhancement patterns, but angiomyolipoma tends to be more homogeneously hypointense and of lower signal intensity in HBP, as it does not contain hepatocytes, whereas HCC contains hepatocytes with various degrees of malignant change.…”
Section: Hepatocellular Carcinoma Versus Nonhepatocellular Tumoursmentioning
confidence: 99%